Elastic energy and optimal stride frequency in running: The effects of uphill and downhill - Snyder, K. L.; Farley, C. T. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
Each runner strongly prefers a stride frequency that is close to the `optimal` stride frequency that minimizes metabolic cost (Cavanagh and Williams, 1982). We investigated the role of elastic energy recovery in determining the optimal stride frequency during level and hill running. Because we expected less useful elastic energy storage and recovery in hill running, we hypothesized that altering stride frequency would change metabolic cost less during hill than level running. Further, we hypothesized that increased metabolic cost would cause runners to prefer stride frequencies closer to optimal on an uphill vs. on the level. Finally, we hypothesized that increased impact forces would lead runners to choose stride frequencies faster than optimal on a downhill.